DEVELOPMENT OF POLYHERBAL WITH ANTIOXIDANT ACTIVITY - Deepak, Jain; Anurekha, Jain (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this research was to develop a polyherbal formulation (PHF) using four different herbs and to evaluate their phytochemicals, physical constants, and determination of their antioxidant activity by DPPH method. Methods: The PHF authenticated herbs were characterized by studying its morphological and pharmacognostic characters. Phytochemical screening showed the presence of alkaloids, glycosides, carbohydrates, amino acid, tannin, steroids, and flavonoids in the combination extract. Physical parameters such as loss on drying (LOD), pH, ash values, LOD, and extractive value have been studied. The antioxidant activity of the combination of extract (100 mg each) was determined using DPPH free radical scavenging method. Results: The results showed that the combination extract has best antioxidant effect at a dose of 400 Î¼g/ml when it was compared with ascorbic acid as the reference standard. Conclusion: The results obtained in this research work clearly showed that the combination extract has best antioxidant effect at a dose of 400 Î¼g/ ml when it was compared with ascorbic acid as the reference standard. Â 